Estudo químico das sementes de bacuri. - Silva Bentes, M. H.; Serruya, H.; Rocha Filho, G. N.; Oliveira Godoy, R. L.; Silva Cabral, J. A.; Maia, J. G. Soares (Acta Amazonica, 1986)
The comparative analysis of the seeds of bacuri and bacuripari show,with respects to the fat content, diferences in the quantitative composition of theirs fatty acids (palmitic 44,2:42,3, palmitoleic 13,2:1,0, stearic 2,3:4,6, oleic 37,8:39,9 and linoleic acids 2,5:12,2; %:%, respectively), and the fact that tripalmitin is present in the fatty extracts of bacuri seeds, in appreciable quantities (10%). These fats, especially from bacuri seeds, can be recommended as alternative sources for industry.